2011
DOI: 10.1042/cbi20100507
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of apoptosis and DNA damage in bovine cumulus cells after exposurein vitroto different zinc concentrations

Abstract: The purpose of this study was to investigate the effect of Zn (zinc) concentration on CCs (cumulus cells) during in vitro maturation. For this purpose, DNA integrity of CCs by addition of different Zn concentrations [0 (control); 0.7 μg/ml (Zn1); 1.1 μg/ml (Zn2) and 1.5 μg/ml (Zn3)] to the culture medium was evaluated by comet assay. In addition, early apoptosis was analysed by annexin staining assay. CCs treated with Zn showed a significant decrease in the DNA damage in a dose-dependent manner. Comet assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The precise contribution of Zn reuptake in mammary gland Zn metabolism is not understood but it clearly plays a critical role in mammary gland Zn metabolism Zip3‐null mice (Kelleher et al, 2009) (as well as Zip1‐null mice; SLK, unpublished observations) have serious defects in mammary gland morphology. Mammary gland function is dependent upon the maintenance of a highly differentiated secretory cell‐type and we speculate that Zn signaling from the previously secreted milk pool, plays a novel and key role in regulating processes essential to maintaining differentiation such as modulating ATP biogenesis (Lemire et al, 2008), regulating apoptosis (Anchordoquy et al, 2011) and regulating Zn‐finger transcription factors such as Egr1 and Egr2 which are critical for cellular differentiation (Boyle et al, 2009). Further studies are needed to explore the relevance of Zn reuptake on mammary cell function.…”
Section: Discussionmentioning
confidence: 99%
“…The precise contribution of Zn reuptake in mammary gland Zn metabolism is not understood but it clearly plays a critical role in mammary gland Zn metabolism Zip3‐null mice (Kelleher et al, 2009) (as well as Zip1‐null mice; SLK, unpublished observations) have serious defects in mammary gland morphology. Mammary gland function is dependent upon the maintenance of a highly differentiated secretory cell‐type and we speculate that Zn signaling from the previously secreted milk pool, plays a novel and key role in regulating processes essential to maintaining differentiation such as modulating ATP biogenesis (Lemire et al, 2008), regulating apoptosis (Anchordoquy et al, 2011) and regulating Zn‐finger transcription factors such as Egr1 and Egr2 which are critical for cellular differentiation (Boyle et al, 2009). Further studies are needed to explore the relevance of Zn reuptake on mammary cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Among these trace elements, zinc, copper, and manganese play an essential role in reproduction. It has been demonstrated that low concentrations of zinc and copper during in vitro maturation (IVM) induce apoptosis and affect the DNA integrity of cumulus cells, which negatively influence the developmental competence of bovine oocytes (Anchordoquy et al, 2011;Picco et al, 2010Picco et al, , 2012. However, adequate zinc (1.5 g/mL) and manganese (6 ng/mL) concentrations during IVM increased the intracellular glutathione concentrations and protect the bovine COCs from apoptosis (Anchordoquy et al, 2014;Picco et al, 2010).…”
Section: Maternal Nutritionmentioning
confidence: 98%
“…More specifically, copper (Cu), iodine (I), manganese (Mn), selenium (Se), and Zinc (Zn) all participate in reproductive processes and are crucial for early embryonic development (Hostetler et al, 2003). Supplementation with Zn, Mn, and Cu improves cumulus-oocyte complex (COC) maturation, reduces apoptosis of cumulus cells, and increases the success of early embryonic development through the blastocyst stage in multiple species including the mouse, cow, pig, and human, when incorporated into in vitro embryo production systems (Gao et al, 2007; Anchordoquy et al, 2011, 2014a, 2014b; Ménézo et al, 2011; Picco et al, 2012; Jeon et al, 2014; Geravandi et al, 2017). Trace minerals have been shown to play a role in the formation of metalloenzymes, which are important in several metabolic processes, including lipid metabolism, glucose utilization, DNA synthesis and transport, and free radical metabolism (Cunnane et al, 1993; De Haan et al, 1994; Townsend et al, 1994; Jovanovic-Peterson and Peterson, 1996; Hostetler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%